Injury and Illness Data for Illinois Mining Industry Employees, 1990 to 2012. Issue 12 (December 2015) - Mabila, Sithembile L.; Gracia, Gabriela; Cohen, Robert; Almberg, Kirsten; Friedman, Lee S.
Abstract : Objective: This study identifies and evaluates injury types associated with distribution of cause of injuries and compensation among Illinois miners. Methods: Cases were selected from the Illinois Workers' Compensation database from 1990 to 2012 to determine injury distributions and compensation among miners and non-miners. Logistic models were used to analyze total monetary compensation, temporary total disability (TTD), and permanent partial disability as primary outcomes. Results: The major predictors of total monetary compensation in both miners and non-miners were TTD, permanent partial disability, average weekly wage, and age at the time of filing. Systemic injuries were an additional driver of final monetary compensation among miners. Miners were compensated $618 less (total monetary compensation; confidence interval 95%: −971, −266; P  < 0.001), had 2.1 more weeks away from work (TTD; confidence interval 95%: 1.58, 2.63; P  < 0.001), and had higher numbers of systemic injuries than non-miners. Conclusions: Systemic injuries are important drivers for TWC in miners in terms of median compensation and TTD.